AN ANALYSIS OF THE THE MAIN FACTOR WHICH SUPPORTING THE CONTENTS OF THE ENGLISH TEXTBOOK BY KEMENDIKBUD - Diah Paramita Efendi; Nuri Ati Ningsih; Brigitta Septarini Rahmasari (PENERBIT LAFADZ JAYA, 2022)
This research was conducted to determine whether the content of the textbook has the same supporting factors to support learning. The textbook is an English textbook used by high school students in the tenth grade. This study aims to find the main factors supporting the content of English textbooks. The methodology used in this study is qualitative research and uses documents as analysis material. In addition, researchers used checklist evaluation to collect data. This study used 10 criteria. From the results of the study, it can be seen that out of 10 criteria, 9 were met. The results of the analysis show that 90% of main factors are functioning properly. The good category was obtained because the total score of the percentage was more than 82.64%. There are 10% or 1 criterion that does not meet the criteria related to encourages seeking further information. From the results of this study, researchers recommend conducting other analysis related to the content of the textbook by conducting an analysis of the validity of the textbook. An analysis that can be done in english textbooks to find out the quality of textbooks.